Bifunctional Separator Coated with Hexachlorocyclotriphosphazene/Reduced Graphene Oxide for Enhanced Performance of Lithium–Sulfur Batteries. Issue 51 (17th August 2018) - Zheng, Yanping; Fan, Honghong; Li, Huanhuan; Fan, Chaoying; Yuan, Haiyan; Yang, Zhifang; Huang, Kecheng; Li, Wenliang; Zhang, Jingping
Abstract: Although extensive research has been performed in the field of Li−S rechargeable batteries, commercial applications are still hindered by the dissolution of the reaction intermediates of lithium polysulfides (LiPSs). Through the combination of experimental and theoretical results, a bifunctional separator has been designed by coating hexachlorocyclotriphosphazene (HCCP)‐decorated reduced graphene oxide (rGO), which provides effective anchor sites for immobilizing the LiPSs. LiPSs can be adsorbed on the HCCP/rGO surface with moderate binding strength, and their structures and the electrical conductivity of HCCP/rGO are well maintained. The synergetic effect of the effective barrier and good electrical conductivity within the HCCP/rGO sheets efficiently anchors LiPSs and achieves enhanced electrochemical performance. More importantly, different substituents can be used to tune the immobilization of LiPSs by HCCP derivatives. Therefore, it is expected that HCCP and its derivatives can be utilized as a promising anchoring material for high‐performance Li−S batteries. Abstract : Bifunctional separator : The synergetic effect of an effective barrier and good conductivity involved in hexachlorocyclotriphosphazene‐decorated reduced graphene oxide (HCCP/rGO) separators can efficiently anchor lithium polysulfides and enhance the performance of a lithium–sulfur battery (see figure).